PENGGUNAAN MEDIA POWTOONTERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA SMP - Lastri Marito Marbun Lastri (Jurnal Pendidikan Sang Surya, 2024)
This research aims to determine the effect of using Powtoon media on the ability to write explanatory texts for class VII students at SMP Negeri 37 Medan. This type of research is quantitative experimental research with a one group pretest posttest design. Quantitative research is research that is based on calculating statistical figures in its findings. The population in this study were all class VII students with a total of 188 students with the sample for this research being VII-D with 30 students determined using a simple random sampling technique. The data analysis technique used is the normality test, homogeneity test and hypothesis test. After conducting research for pretest and posttest experiments using Powtoon media, the average score for the pretest class was 54.53 with a variance of 151.29 and the posttest class average was 69.86 with a variance of 217.26. The pre-test and post-test data prerequisite test results stated that the sample had a normal and homogeneous distribution. From the results of testing the research hypothesis, a "t" test was carried out at a significant level of α= 0.05, obtained Tcount > Ttable = (4.31 > 2.045). Thus the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted. So it can be concluded that there is a significant influence on the use of Powtoon media in class VII SMP Negeri 37 Medan.